2014
DOI: 10.4196/kjpp.2014.18.4.321
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of the Nuclear Factor Kappa B Inhibitor Pyrrolidine Dithiocarbamate on Experimental Testicular Torsion and Detorsion Injury

Abstract: Testicular torsion results with the damage of the testis and it is a surgical emergency. Pyrrolidine dithiocarbamate (PDTC) is a low-molecular-weight antioxidant and potent inhibitor of nuclear factor kappa B (NF-κB) activation. In this study, we aimed to investigate the effects of PDTC to testicular torsion-detorsion (T/D) injury. Forty adult male Sprague-Dawley rats were separated into four groups. A sham operation was performed in group I. In group II, torsion is performed 2 hours by 720 degree extravaginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Various physiopathological mechanisms have been put forward to explain the tissue damage that occurs during ovarian torsion and detorsion including ovarian lipid peroxidation, vascular leucocyte margination and apoptosis . The detorsion involves the production of toxic reactive oxygen species (ROS) with the return of blood flow following ischemia . Overproduction of ROS could lead to a significant elevation in lipid peroxidation, thereby generating MDA and destroying the antioxidant defense systems of the human body .…”
Section: Discussionmentioning
confidence: 99%
“…Various physiopathological mechanisms have been put forward to explain the tissue damage that occurs during ovarian torsion and detorsion including ovarian lipid peroxidation, vascular leucocyte margination and apoptosis . The detorsion involves the production of toxic reactive oxygen species (ROS) with the return of blood flow following ischemia . Overproduction of ROS could lead to a significant elevation in lipid peroxidation, thereby generating MDA and destroying the antioxidant defense systems of the human body .…”
Section: Discussionmentioning
confidence: 99%
“…Levels of malondialdehyde (MDA), an indirect marker of cellular injury that reflects the extent of systemic lipid peroxidation in the heart, were measured by the method by Oshawa et al 18 In brief, heart samples were collected at baseline and during the post-IR period and then homogenized in phosphate buffered saline (PBS) (1:5, w/v) using a mini homogenizer (MICCRA-D1, Germany). Tissue homogenates were centrifuged (1,000 g, 4 ºC, 10 min) and supernatants were collected for measurement of MDA levels; 2.5 mL of trichloroacetic acid (20%) was added to 0.5 mL of supernatant followed by addition of 1 mL of thiobarbituric acid (0.67%).…”
Section: Methodsmentioning
confidence: 99%
“…Contrastingly, the expression of Apo A1 was downregulated compared to the control group. However, when mice were intraperitoneally injected with PDTC, which may attenuate the inflammatory response by inhibiting NF-κB, all of the changes induced by LPS were reversed (19,20). These results indicated that sepsis directly affected the SM and cholesterol content, and the expression of these proteins in the livers of mice.…”
Section: Discussionmentioning
confidence: 65%
“…To clarify the metabolism of SM and cholesterol in the liver during sepsis in the present study, BALB/c mice were treated with LPS (to induce sepsis), LPS + pyrrolidine dithiocarbamate (PDTC) or PBS. PDTC inhibits the activation of NF-κB specifically by suppressing the release of the inhibitory subunit IκB combining with NF-κB (19,20). SM and cholesterol content, SMS activity and related protein levels were measured.…”
Section: Introductionmentioning
confidence: 99%